The Mediating Role of Physical Activity and Self-Rated Health in the Association Between Depression and Quality of Life in Older Europeans: An Analysis Differentiated by Sex - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Objectives: This study investigates the mediating role of moderate physical activity (MPA), vigorous physical activity (VPA), and self-rated health (SRH) in the association between depression and quality of life (QoL) in a large sample of Europeans aged 50 and over, differentiated by sex. Methods: Data from the 2017 Survey of Health, Ageing and Retirement in Europe were analyzed, including 11,986 individuals (6843 women) aged 50 and older. All information was collected through face-to-face interviews: sociodemographic data, SRH, physical activity levels, depression (EURO-D scale), and QoL (CASP-12). Results: Comparatively, women reported a higher prevalence of depression, a lower perception of QoL, and slightly lower levels of SRH, MPA, and VPA. Parallel mediation models revealed, for both sexes, that an increase in VPA levels was more effective in benefiting SRH; and MPA proved to be a better promoter of QoL. When comparing sexes, only the path depression → VPA → QoL showed a significant difference (p < 0.001). Conclusions: These results provide valuable insights for developing physical activity interventions capable of improving mental health and promoting QoL in older European adults. © 2024 by the authors.